Pembentukan dan Pemberlakuan AAUPPL Melalui Penyelenggaraan Pemerintahan dalam Rangka Menjelmakan Pemerintahan yang Baik dan Bersih di Indonesia - marbun SF (Fakultas Hukum Universitas Islam Indonesia, 2001)
The general principles making and expiry of good governance through governmental actions has an important thing for nationailife its implementation jurisdictionaly and sociologically as a political norm forbureaucracyinthe centralorprovincial government has been regulated by a presidential and governor decree which based upon conventionalpractices of governance. Theimpact of neglecting this matter wouidcause any dismissal by Administrative Court.